(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This article discusses the insolvency of company groups and the effect of the original bankruptcy declaration or that of a subsidiary of the group, that is, how it the group is affected by the dominant company or one of the dominant companies is declared bankrupt. This matter is not resolved in the doctrine nor in the Insolvency Act itself, departing from the fact a unitary concept of the group does not exist. The solution sought by debt subordination in the insolvent company of the persons specifically related to it, does not seem adequate.